53‐5: Late‐News Paper: a‐IGZO TFT Based Active Matrix Pressure Sensor by Integrating ZnO Nanowires as Sensing Unit. Issue 1 (25th September 2020) - Shi, Xuewen; Lu, Congyan; Zhang, Li; Geng, Di; Li, Ling; Pan, Caofeng
Abstract : In this paper, we demonstrated an amorphous indium‐gallium‐zinc‐oxide thin film transistors (a‐IGZO TFTs) based active matrix touch sensor array by integrating ZnO nanowires (NWs) as pressure sensitive materials. ZnO NWs servicing as a piezoelectric material shown superior mechanical‐electric transition performance as well as excellent compatibility with TFT process. The ZnO NWs were connected with switching TFT in series. When a pressure was applied on sensor unit, the deformation of ZnO NWs would induce change of resistance or metal‐semiconductor barrier height between ZnO NWs and contact metal, thus the current following through pressure unit would change. By using this method, we accurately mapped pressure change in a region of 1.4cm*1.4cm 2 . The demonstration in this work gave a possible solution for integrating pressure sensor in display panel in future applications.